MODEL PERENCANAAN PEMBANGUNAN DAERAH SECARA TIMBAL BALIK (RECIPROCAL DEVELOPMENT PLANNING): Belajar dari Model “Gerbang Dayaku” di Kabupaten Kutai Kartanegara - Nugraha, Drs. (Pusjar SKPP Lembaga Administrasi Negara, 2005)
The idea of “development from below” (bottom up development planning) has been widely believed as the single answer for the dysfunctional of “development from above” (top-down development planning). Such understanding is not applicable for all cases, however. Empirical evidence shows that the main source of development failures is incompatibility of people’s needs and wants with elite’s decision. In such a case, public participation in the development process has been neglected. As a matter of fact, active participation from the people constitutes one of key successes for the development activities in many countries. Being learnt from the model of “two-stages development planning” in Kutai Kartanegara called Gerbang Dayaku, it can be recapitulated that reciprocal development planning is a requirement to mend the development mechanism stipulated in the Law No. 25/2004 concerning National Development Planning System.